JEJAK KESULTANAN BANTEN DI LAMPUNG ABAD XVII (Analisis Prasasti Dalung Bojong) - Wijayati, Mufliha (Universitas Islam Negeri Raden Intan Lampung, 2011)
Lampung is the pepper-producing areas that had been under seizing of kingdoms of the surrunding since long time. The arrival of Islam in Lampung, in a lot of analysis, is also closely related to its existence as the pepper-producing area. When the Port of XVI-XVII centuries Banten grown into an international center for trade with commodities and spices, especially pepper, then for the supply of the pepper, it later expanded into a number of pepper-producing regions, including Lampung. A number of policies applied to pepper-producing regions, including tying a number of rules in the population with a charter granted to the representative retainer of Banten in the area, one of them in the context of Lampung is the Charter Dalung Bojong which is the object study of this article. Using archeological history approach, the present author attempted to uncover the elements contained in the inscription as historical sources that provide information about the events of political, bureaucratic, religious, and the life of the community in the past. It is revealed that the charter issued in 1102 H/1691 M by Sultan Abul Mahasin Muhammad Zainul Abidin (1690-1733 AD) contains regulations of forced cultivation of pepper, the pepper trading regulations, and also contains civil and criminal laws. On the other hand, this inscription also reveals a pattern of Jakarta-Lampung relationship in the seventeenth century: in terms of political, economic, social and cultural rights.